2007
DOI: 10.1902/jop.2007.060280
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Implant Surfaces on Peri‐Implant Osteogenesis: Histomorphometric Analysis in Sheep

Abstract: Our results suggest that, in the early period of peri-implant healing, the implant surface morphology that seemed to influence the increase of peri-implant osteogenesis, bone turnover, and peri-implant bone maturation was SLA-60. We suggest that this surface, characterized by moderately deep titanium cavities very similar to the osteocyte lacunae, could act as a microscopic scaffold for mesenchymal and/or osteoblast-like cells adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 46 publications
0
49
2
3
Order By: Relevance
“…[32] Despite the differences in the osseointegration times, the bone characteristics, the size of implants or other less influential parameters, the overall patterns of healing are similar to those found in other studies using the sheep model. [33][34][35] All micro-CT parameters measured showed unambiguous increments in the bone turnover on and around the calcium modified surfaces with respect to the controls. In general, these test surfaces achieved more vertical bone growth, both ectopic and towards the marrow.…”
Section: Discussionmentioning
confidence: 85%
“…[32] Despite the differences in the osseointegration times, the bone characteristics, the size of implants or other less influential parameters, the overall patterns of healing are similar to those found in other studies using the sheep model. [33][34][35] All micro-CT parameters measured showed unambiguous increments in the bone turnover on and around the calcium modified surfaces with respect to the controls. In general, these test surfaces achieved more vertical bone growth, both ectopic and towards the marrow.…”
Section: Discussionmentioning
confidence: 85%
“…In using a similar surface to SLA, a recent study showed that the implant surface morphology seemed to influence the increase of osteogenesis. These implant surfaces, characterized by moderately deep cavities that are very similar to the osteocyte lacunae, could act as a microscopic scaffold for mesenchymal and/or osteoblast-like cell adhesion (Franchi et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Also the implant surface treatment modalities increase the primary stability, since an increase in roughness may improve the contact between the bone and the implant. In addition, in vitro studies have shown that the sandblasted and etched implants promote the osteogenesis by improving the osteoblastic activity, as compared to the machined ones (8)(9)(10). Regarding the quantity and the quality of the bone, there is a consistent literature showing that most of the failures in implantology are more linked to the quality than to the quantity of bone.…”
Section: Introductionmentioning
confidence: 99%